Weeds diversity and the production of shallot (Allium ascalonicum L.) due to the application of azolla fertilizers and oxyfluorfen. Issue 1 (October 2020) - Padjung, R; Syam'un, E; Haring, F; Mantja, K; Kasim, N; Suni, Y
Abstract: The study aimed to determine the growth and production responses of shallot plants to the application of azolla fertilizer and oxifluorfen herbicide. This research was conducted in Balubu Village, Belopa District, Luwu Regency, South Sulawesi (3°23′32″ South latitude and 120°19′56″ East longitude) from February to April 2019. The study site was located at an altitude of 20 meters above sea level with average monthly rainfall of 151-200 mm/month. The study was conducted as experimental research based on a Split Plot Design. Azolla fertilizer was set as the main plot consisted of three levels, namely control, 3, and 6 tons ha −1 and the oxyfluorfen concentration was set as the sub plots consisted of four levels, namely control, 2, 4, and 6 cc L −1 . Each treatment combination was repeated 3 times. The results show that the application of 6 ton per hectare of azolla fertilizer resulted in the highest average plant height at 42 days after planting (27.91 cm), bulb diameter (20.78 mm), bulbs fresh weight per plant (24.72 g), bulbs dry weight per plant (19.73 g), bulbs fresh wet per plot (1112.25 g), bulbs dry weight per plot (888 g), and production per hectare of 8.88 ton ha −1 . Oxifluorfen treatment with a concentration of 6 cc L −1 effectively controlled the dominant weeds of onion plants such as Synedrella nodiflora, Mimosa pudica, and Stachytarpheta jamaicensis with the lowest average number of individual weed per plot of 6.00 weeds.